The Influence of Leadership, Organizational Culture, and Pedagogical Competence on the Performance of State Madrasah Ibtidaiyah Teachers - Kuseini, Ahmad; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the influence of these three variables, both partially and simultaneously, on the performance of teachers at State Islamic Elementary Schools (MIN) in Metro City. The research employed a quantitative approach using multiple regression analysis through SPSS 22.0. The study population consisted of 106 MIN teachers in Metro City, and based on the Slovin formula with a 10% margin of error, 51 samples were selected using the Proportional Random Sampling technique. The instrument used was a Likert-scale questionnaire that had been tested for validity and reliability using the Product-Moment correlation and Cronbach's Alpha, and all variables were found to be valid and reliable. The research sample involved all MIN teachers in Metro City as respondents. The results showed that the principal's leadership has a positive but not dominant influence, organizational culture significantly affects teachers' motivation and work ethic, while pedagogical competence is the strongest factor determining teacher performance, with the highest regression coefficient (0.609). Simultaneously, the three variables contribute significantly to teacher performance (sig. 0.000; F-value 348.204). The findings emphasize that teacher performance improves optimally when leadership is effective, the organizational culture is religious and collaborative, and teachers' pedagogical competence is professionally developed.